Perlindungan Hukum Korban Kekerasan dalam Rumah Tangga - Rahma, Andi (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2013)
Problems of fundamental which is told in this research is how protection of law to Woman Of Victim Doing An Injustice Hardness In Household In town of Makassar, and Factor influencing protection of law to woman of victim to hardness doing an injustice in household.Method the used is approach of sosioyuridis and nature of research is descriptive, in this research which become population is Makassar polrestabes, public attorney of Country of Makassar, district court, office institute legal aid, housemaid employer and victim reside in town of Makassar, there is research sampel specified by purpossive sampling. Data collecting by documentation and interview. obtained data is hereinafter analysed qualitative that is analysis having the character of mendersripsikan.Result of this research indicate that protection of law to woman of hardness doing an injustice victim in household after going into effect law it of No 23 Year 2004 not yet been conducted maximally. Although from 3 hardness case to pemabantu of reported household to police, its of him use law assertion of No23 Year 2004. But existing peripherals not yet walked better.Hardness victim which there is still do not report hardness to role x'self and also society realized by way of change of protection ascription is an work of excellency of daan if knowing the happening of hardness of vinicity environment to be is immediately reported. Factor influencing protection of law to woman of victim to hardness doing an injustice in household. that is by preventif (pencegahan) handled by Bimnas (Tuition Society). While duties of Represif (penindakan of law) executed by part of police detective. Governmental deservedly give attention to more to housemaid by way of forming an regulation of prundang-undangan arranging it.